PERILAKU TAKTIS UNTUK NON - PLAYER CHARACTERS DI GAME PEPERANGAN MENIRU STRATEGI MANUSIA MENGGUNAKAN FUZZY LOGIC DAN HIERARCHICAL FINITE STATE MACHINE - Supeno Mardi Susiki Nugroho; Yunifa Miftachul Arif; Mochamad Hariadi; Mauridhi H Purnomo (Jurnal Ilmiah Kursor, 2011)
Nowadays, the proliferation of game technology especially in intelligent human-like NPCs (Non-Player Characters) leads to more adaptive behavior of NPCs maneuvers. Providing smoother behaviors require comprehensive rules base which can respond to players behaviors. Addressing this requirement we propose NPCs which had tactical behaviors based on fuzzy logic. The fuzzy logic defines four type behaviors for the NPCs, which depend on NPC health, ammo, and distance of the enemy.Those behaviors implemented on two intelligent agents employed Hierarchical Finite State Machine to express the maneuver actions of NPC during combat scenes. Using First Person Game Engine, the performance of NPCs with fuzzy behavior compared with NPC without fuzzy behavior. The results of experiment showed the performance of the NPC with Fuzzy behavior outperform 80% better than the NPC without fuzzy behavior.